Development of a Programme of Musical Activities for the Contribution of Unplugged Computational Thinking in Early Childhood Education - Campollo-Urkiza, Arantza (2023)
Introduction. National and international educational bodies emphasize the importance of developing teaching-learning strategies in classrooms that standardize the use of Information and Communication Technologies in a globalized world. For this reason, programming and robotics have been introduced in classrooms in Spain from early childhood education to higher education as a means of contributing to computational thinking and other approaches such as the STEAM construct in which the arts and sciences converge. Objective. This paper aims to present a program of musical activities for early childhood education with which to contribute to unplugged computational thinking and the language of programming and its relevance in 3-year-old classrooms. Method. This qualitative study presents a didactic proposal with musical activities to develop computational language. These activities were conducted during the 2021-2022 school year in two 3-year-old classrooms in a school in the Community of Madrid, Spain. The participants were 38 students and the two tutors of these classrooms. These two professionals collected information on the categories analyzed and the children’s evaluation items through participant observation and subsequent recordings. Results. The results show a positive development in literacy in programming and robotics, as well as an improvement in spatial reasoning skills, progress in logical thinking, lower limbs motor control, and oculo-manual dexterity. Conclusions. There exists the need to perform programming and robotics activities in contexts and learning situations in pre-school classrooms for the development of computational thinking and interdisciplinary work in all areas of this stage.